Phonological, grammatical, and written words in Wichi - Terraza, Jimena (2014)
This article aims at investigating the linguistic criteria to determine what a word is in Wichi (Matacoan), a polysynthetic and agglutinative language spoken in the Gran Chaco Region, in South America. The main phonological criteria proposed are phonological rules and stress. We also apply some grammatical criteria that have been proposed cross linguistically, some of which are useful to determine the boundaries of grammatical words in Wichi. Finally, we explore the relationship between the phonological and grammatical word with the written word. We base our analysis of written words on a textbook (Tsalanawu) used in many bilingual schools in Northeastern Argentina.